If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 9y + -8y + 5 Reorder the terms: 8 = 5 + 9y + -8y Combine like terms: 9y + -8y = 1y 8 = 5 + 1y Solving 8 = 5 + 1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 8 + -1y = 5 + 1y + -1y Combine like terms: 1y + -1y = 0 8 + -1y = 5 + 0 8 + -1y = 5 Add '-8' to each side of the equation. 8 + -8 + -1y = 5 + -8 Combine like terms: 8 + -8 = 0 0 + -1y = 5 + -8 -1y = 5 + -8 Combine like terms: 5 + -8 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3
| 3x/5+2=-4 | | (7/1)*-13 | | -3x-10x=26 | | 2-(m+4)-6m-3=m-5 | | -17(x+2)+6(4x-4)=6(x-4)+13 | | 4-4y+5y=7 | | s+3=-3 | | -48-96+(-32)=x | | p=mvforv | | v=2.5*1.5*1 | | -8+x=45 | | (2W+5)(-3)= | | 9+5x=2x+8 | | -5+((6)/(x+5))=((1)/((x+5)^2)) | | 6-2x-1=4x+3-6x-3 | | 87-(5x+12)=5(x+4)+x | | -48-96=x | | t/28=4/7 | | -3a+9a=0 | | -30c=45 | | 9+5x=2x+5 | | 1/2n+18=2n | | h-79=-80 | | (11x-6y)-(2x-3y-z)+(2y-4z)= | | 33-a=-54 | | x^2+9x+32=14 | | 9n-3=-48 | | -7/10=-35/A | | 96+(-32)=x | | -6(3x-8)=-8 | | -3.22=60.8 | | 3y-20=-65+8y |